View-dependent accuracy in body mass judgements of female bodies. (March 2018) - Cornelissen, Piers L.; Cornelissen, Katri K.; Groves, Victoria; McCarty, Kristofor; Tovée, Martin J.
Highlights: Previous studies of body image used images of bodies viewed in front-view. Viewing in front-view obscures key visual cues used to judge adiposity. Viewing bodies in three-quarter view combines cues from front and profile. Observers completed a 2-alternative forced choice at 3 different orientations. There is a significant advantage in weight discrimination in three-quarter view. Abstract: A fundamental issue in testing body image perception is how to present the test stimuli. Previous studies have almost exclusively used images of bodies viewed in front-view, but this potentially obscures key visual cues used to judge adiposity reducing the ability to make accurate judgements. A potential solution is to use a three-quarter view, which combines visual cues to body fat that can be observed in front and profile. To test this hypothesis, 20 female observers completed a 2-alternative forced choice paradigm to determine the smallest difference in body fat detectable in female bodies in front, three-quarter, and profile view. There was a significant advantage for three-quarter and profile relative to front-view. Discrimination accuracy is predicted by the saliency of stomach depth, suggesting that this is a key visual cue used to judge body mass. In future, bodies should ideally be presented in three-quarter to accurately assess body size discrimination.